The Effect of Management Compensation and Corporate Governance on Corporate Tax Management - Evy Rahman Utami; Indra Wijaya Kusuma (The Indonesian Journal of Accounting Research, 2013)
This study investigates how corporate governance affects tax management behavior and contributes the literature on corporate governance. First, this study examines directors compensation and directors ownership, as corporate governance mechanism of a firm, in managing taxes to increase performance. Second, to the best of our knowledge, this is the first study in Indonesia investigating the link between managerial compensation to tax management. This study finds that directors ownership exhibits a significance relationship in reducing cash tax paid. But, directors compensation does not result lower taxes paid and it is seems not an effective mechanism in engaging tax management. Implementing corporate governance mechanism also will not result in lower taxes because corporate governance induces managers to be more careful in managing taxes.